Z ìstorìï formuvannâ Ukraïns'koho pravopisu Amvrosìj Metlins'kij ta Pantelejmon Kulìš - Kocsis Mihály (2021)
The present paper investigates what role the university professor Amvrosy Metlinsky and writer Panteleymon Kulish played in the history of modem Ukrainian orthography, concluding that the scientific community’s evaluation of these two persons has changed greatly in the past 150 years. The role of Metlinsky and the circle of Kharkiv intellectuals he was in contact with has been devalued, while that of Kulish has gained importance, perhaps overly so.
Keywords: Bölcsészettudományok; Nyelvek és irodalom